Power Profiles and In Vitro Optical Quality of Scleral Contact Lenses: Effect of the Aperture and Power. Issue 3 (May 2018) - Domínguez-Vicent, Alberto; Esteve-Taboada, Jose Juan; Recchioni, Alberto; Brautaset, Rune
Abstract : Objective: To assess the power profile and in vitro optical quality of scleral contact lenses with different powers as a function of the optical aperture. Methods: The mini and semiscleral contact lenses (Procornea) were measured for five powers per design. The NIMO TR-1504 (Lambda-X) was used to assess the power profile and Zernike coefficients of each contact lens. Ten measurements per lens were taken at 3- and 6-mm apertures. Furthermore, the optical quality of each lens was described in Zernike coefficients, modulation transfer function, and point spread function (PSF). A convolution of each lens PSF with an eye-chart image was also computed. Results: The optical power fluctuated less than 0.5 diopters (D) along the optical zone of each lens. However, the optical power obtained for some lenses did not match with its corresponding nominal one, the maximum difference being 0.5 D. In optical quality, small differences were obtained among all lenses within the same design. Although significant differences were obtained among lenses ( P <0.05), these showed small impact in the image quality of each convolution. Conclusions: Insignificant power fluctuations were obtained along the optical zone measured for each scleral lens. Additionally, the optical quality of both lenses has showed to be independent of the lens power within the same aperture.